KEPRIBADIAN TOKOH UTAMA MAT DAWUK DALAM NOVEL DAWUK KISAH KELABU DARI RUMBUK RANDU KARYA MAHFUD IKHWAN [The Personality of Mat Dawuk as Main Figure in the Novel Dawuk Kisah Kelabu dari Rumbuk Randu by Mahfud Ikhwan] - Tito Tri Kadafi (Kantor Bahasa Provinsi Maluku, 2021)
This research uses descriptive qualitative method with reading-note technique as data collection technique. The research data is taken from the narrative of the character Mat Dawuk in the novel Dawuk Kisah Kelabu dari Rumbuk Randu by Mahfud Ikhwan, which is analyzed using Sigmund Freud's theory of psychoanalysis. The results showed that the personality structure of the Mat Dawuk character was influenced by three personality systems, namely the id, ego, and superego. His preference in Mat Dawuk's id is Mat Dawuk's libido drive towards Inayatun. The ego that appears in Mat tries to realize and fulfill what the id wants, resulting in an attitude of loyalty, protection, until even Mat Dawuk pledges that Inayatun is a power within him - that power disappears after Inayatun dies, which is illustrated through a willing attitude. Mat to be persecuted. The superego, which acts on the principle of morality, is here to help in making decisions about what the id wants, and also helps the ego to control the id that is wanted to be fulfilled. The Mat Dawuk character also has a living instinct that comes from Inayatun. Meanwhile, after Inayatun died, Mat tended to be controlled by a dead instinct which made him helpless, and chose to withdraw from society. Not only that, the character Mat Dawuk is depicted as experiencing anxiety several times, which later will correlate with Mat's personal development in survival, or what is known as a defense mechanism, and Mat Dawuk's tendency to be in aggression and repression mechanisms. Penelitian ini menggunakan metode kualitatif deskriptif dengan teknik baca-catat sebagai teknik pengumpulan datanya. Data penelitian diambil dari pengisahan tokoh Mat Dawuk dalam novel Dawuk Kisah Kelabu dari Rumbuk Randu karya Mahfud Ikhwan, yang ditelaah menggunakan teori psikoanalisis Sigmund Freud. Hasil penelitian menunjukkan struktur kepribadian tokoh Mat Dawuk dipengaruhi oleh tiga sistem kepribadian yakni id, ego, dan superego. Id dalam diri Mat Dawuk preferensinya adalah dorongan hasrat libido Mat Dawuk terhadap Inayatun. Ego yang muncul pada diri Mat berusaha mewujudkan dan memenuhi apa yang diinginkan oleh id, sehingga timbul sikap kesetiaan, melindungi, hingga bahkan Mat Dawuk mengikrarkan bahwa Inayatun adalah kekuatan di dalam dirinya – kekuatan itu pun hilang, setelah Inayatun meninggal, yang digambarkan melalui sikap rela Mat untuk dipersekusi. Superego yang bertindak berdasarkan prinsip moralitas, hadir untuk membantu dalam pengambilan keputusan apa yang diinginkan oleh id, serta turut membantu ego untuk mengendalikan id yang bersifat ingin dipenuhi. Tokoh Mat Dawuk juga memiliki insting hidup yang berasal dari Inayatun. Setelah Inayatun meninggal, Mat cenderung dikuasai oleh insting mati yang membuatnya tidak berdaya, dan memilih menarik diri dari masyarakat. Tak hanya itu, tokoh Mat Dawuk digambarkan beberapa kali mengalami kecemasan, yang nantinya akan berkorelasi dengan perkembangan kepribadian Mat dalam bertahan hidup, atau disebut sebagai mekanisme pertahanan, dan kecenderungan Mat Dawuk berada pada mekanisme agresi dan represi.